Influence of solution pH on the formation of iron oxide nanoparticles - Suppiah, Durga Devi; Johan, Mohd Rafie (IOP Publishing, 2019)
Iron oxide phase orientation were highly influenced by solution pH, crystalline structure, purity, surface enrichment, particle size, and morphology. This paper investigates the influence of pHchanges by varying the precursor anions of chloride (FeCl2) and sulphate (FeSO4) on the formation of iron oxide nanoparticles using one step controlled precipitation technique. The obtained titration curve provided vital information on the reaction mechanism whereby different hydrolysis rate of precursor leads to different iron oxide phases. It was determined that at pH 4, goethite (α-FeOOH) was obtained. Continuous addition of hydroxyl ions (OH−) then forms iron hydroxides (Fe(OH)2) which will then subsequently react with the goethite precipitating magnetite (Fe3O4) nanoparticles (35–45 nm) atpH 10 with ferromagnetic behavior. By the use of Cl− anion, the slower hydrolysis process induced requires more hydroxyl ions to reach pHequilibrium leading to larger maghemite nanoparticles (50–60 nm). Spectroscopic analysis via Raman and FTIR analysis confirms the phases obtained. SEM andTEMimaging shows the correlation of structure orientation anisotropy which influenced the magnetic properties. Spherical magnetite nanoparticles strong dipolar interaction have higher coercivity (117G) and remanence (12 emu g−1) compared to the synthesised maghemite spinel needle-like structure nanoparticles. The understanding of the iron oxide structure directing effect by complex pH solution mechanism was essential for not only to prepare different forms of iron oxide and hydroxides but also controlled synthesis reproducibility.